A COMPARISON OF SALIVARY CORTISOL LEVELS IN PATIENTS WITH AND WITHOUT PERIODONTAL DISEASE (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the association between salivary cortisol levels and periodontal disease.Methods: A cross-sectional study was conducted on 174 patients who visited the Ho Chi Minh city Hospital of Odonto-Stomatology for examination and treatment. They were divided into 3 groups: H (healthy periodontal tissue), G (gingivitis), P (periodontitis).  Periodontal tissue was examined and PPD, CAL, BOP, and PI indices were recorded; unstimulated saliva samples were taken. The significance threshold p < 0.05 was applied to all statistical tests.Results: Salivary cortisol levels were significantly greater in the 2 periodontal disease  groups compared to the healthy group, with group G showing the highest level (p < 0.05). No association was found between salivary cortisol and BOP, PI, and severity of periodontal disease  (p > 0.05).Conclusion: An initial association was discovered between salivary cortisol levels and the presence or absence of periodontal disease. Further research is needed to better define the association between cortisol and periodontal disease.
Keywords: Salivary cortisol levels, periodontal disease, psychological stress, salivary biomarkers.